Pemanfaatan Mobile Health Dalam Mendukung Pelayanan di Area Onkologi Anak: Literatur Review - Faidah, Putry Nur; Wildani, Andi Amalia (Universitas Fort De Kock Bukittinggi, 2021)
Introduction : Cancer is the second leading cause of pediatric death in developed countries. Chemotherapy as the main therapy cause various side effects and complications. Interventions such as health education, symptoms management and psychological social support are important elements in care process. Mobile Health is a mobile application provides various features are very accessible and children can involved actively in the care process. Purpose : To describe the usability of mobile health in supporting services of pediatric oncology area. Methods : Using a literature review method on 10 articles searched through PROQUEST, EBSCO, Science Direct, JMIR, and Spingerlink database from 2018 to 2021. Results : Mobile health is effective and provides benefits in health education, symptoms reporting and management, pediatric and caregiver support. Recommendation : Mobile health allows to be used in Indonesia to support pediatric oncology services. Keywords: adolescent, cancer, mobile health, pediatric.